Implementation of food labelling policy in small, medium and micro food businesses in West Nusa Tenggara - Ayuningtyas, Dumilah; Farida, Ida; Utami, RR Mega; Barinda, Sandra; Munawaroh, Sayyidatul (Universitas Udayana, 2021)
Background and purpose: The government has adopted policies regarding food labelling to ensure food quality and safety, but the implementation has not yet optimal. This study identifies resources, knowledge, and facilities that affect food labelling implementation in small, medium, and micro food-businesses (SMMF-B) in West Nusa Tenggara, Indonesia. Methods: We conducted a mixed method study. The qualitative data was collected through in-depth interviews with informants from the West Nusa Tenggara Provincial Office of National Agency of Drug and Food Control and the Mataram City. Health Office, and a focused-group discussion involving SMMF-B owners. The quantitative data was collected with a survey to 30 respondents using questionnaire and observation of the label of 36 SMMF-B products to determine the presence of product’s label, composition, net-weight, producer’s name and address, production code, expiry date and distribution license. Results: We found SMMF-B owners’ knowledge on food labelling was low, however, they expressed supports to the implementation of food label controlling. Of the 36 food labels, the two highest number of violations were the absence of production code (88.9%) and net weight (86.1%). Meanwhile, of the 30 surveyed respondents, the majority (96.6%) stated the importance of labels on SMMF-B products and almost two third (63.4%) read food labels before purchasing the product. Conclusion: This study reveals that SMMF-B in West Nusa Tenggara has not implemented food labelling policies optimally. The lack of implementation was influenced by the government’s lack of funds and minimal information and monitoring efforts. Therefore, government should increase budget allocation for food label controlling, number and capacity of food label controllers and strengthen the enforcement.